Development of Polyethylene Glycol Diacrylate-Based Micropattern Substrate to Study the Interplay Between Surface Topography and Cellular Response for Tissue Engineering Applications - Mohd Darwis; Victoria Levario-Diaz; Sadaf Pashapour; Jonah Voigt; Eloïse Lebaudy; Norhayati Sabani; Ahmad Bakar; Nihal Vrana; Philippe Lavalle; Elisabetta Cavalcanti-Adam; Siti Ngalim (Bio-Protocol)
A key goal in the bioengineering field is the development of surface patterning of proteins that guide and control cellular organization. To this end, we developed a method to create a microstructured hydrogel based on soft-lithography techniques using polydimethylsiloxane (PDMS) and polyethylene glycol diacrylate (PEGDA). This approach involves the design of microfluidic geometries using graphical software, employing PDMS as a mold and leaving PEGDA as a substrate for the fabrication of microstructures and, thus, patterning extracellular matrix (ECM) proteins to promote cell adhesion. The combination of these techniques allows the fabrication of hydrogel microstructures without following conventional photolithography methods, such as the use of a photomask, the alignment required to produce the patterns, and the associated expenses. This study highlights the versatility and potential of PEGDA-based hydrogels as platforms to advance tissue engineering strategies.